Internationalization of MSME through Property Rights: A Study Case of Food Stall - Tengku Kespandiar; Sudarmiatin Sudarmiatin; Imam Mukhlis (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this study is to find out the internationalization of MSMEs from a review of property rights in case studies of simple food stalls. The data collection method was carried out qualitatively through field observations, interviews and documentation in the process of interviewing 3 informants. The sampling technique in this study is quota sampling. The data analysis technique used in this study is descriptive analysis and explorative analysis and then processed using the Atlas qualitative data analysis tool. The results of this study support the internationalization of Simple Restaurants, because there are several indicators of innovation, business environment, and internationalization that can influence the internationalization process of Simple Dining Stalls to fulfill the desired desires. This indicates that the process was successful.